Cut‐off value of nuchal translucency as indication for chromosomal microarray analysis. (26th July 2017) - Maya, I.; Yacobson, S.; Kahana, S.; Yeshaya, J.; Tenne, T.; Agmon‐Fishman, I.; Cohen‐Vig, L.; Shohat, M.; Basel‐Vanagaite, L.; Sharony, R.
ABSTRACT: Objectives: An association between isolated, increased nuchal translucency thickness (NT) and pathogenic findings on chromosomal microarray analysis (CMA) has been reported. A recent meta‐analysis reported that most studies use a NT cut‐off value of 3.5 mm. However, considering NT distribution and the commonly accepted 5% false‐positive rate in maternal serum screening, NT cut‐off levels should be reconsidered. The aim of this study was to assess different NT cut‐off levels as indication for CMA and to determine whether CMA should be recommended for mildly increased NT of 3.0–3.4 mm. Methods: This was a retrospective, multicenter study of singleton pregnancies with CMA results and either normal NT and no other finding or with increased NT as the only medical indication for CMA at the time of an invasive procedure (increased NT was considered an isolated finding in cases of advanced maternal age). Women with normal fetal NT who underwent CMA did so at their own request. A single laboratory performed all genetic analyses. Comparative genomic hybridization microarray analysis or single nucleotide polymorphism array technology was used for CMA. If combined first‐trimester screening (NT and biochemistry) indicated increased risk for common aneuploidies, the case was excluded. NT was used to divide cases into three groups (≤ 2.9 mm, 3.0–3.4 mm and ≥ 3.5 mm) and their CMA results were compared. Results: CMA results were recorded in 1588 pregnancies, among which 770 fetuses had either normal NT with no other finding or isolated increased NT. Of these, 462 had NT ≤ 2.9 mm, 170 had NT of 3.0–3.4 mm and 138 had NT ≥ 3.5 mm. Pathogenic copy number variants were found in 1.7%, 6.5% and 13.8% of cases, respectively. Conclusion: Our results suggest that CMA should be recommended when fetuses have isolated, mildly increased NT (3.0–3.4 mm). Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 50: 293–294